2015
DOI: 10.1111/1462-2920.12707
|View full text |Cite
|
Sign up to set email alerts
|

Functional adaptations of the bacterial chaperone trigger factor to extreme environmental temperatures

Abstract: Summary Trigger factor (TF) is the first molecular chaperone interacting cotranslationally with virtually all nascent polypeptides synthesized by the ribosome in bacteria. Thermal adaptation of chaperone function was investigated in TFs from the Antarctic psychrophile Pseudoalteromonas haloplanktis, the mesophile Escherichia coli and the hyperthermophile Thermotoga maritima. This series covers nearly all temperatures encountered by bacteria. Although structurally homologous, these TFs display strikingly distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…For example, the predicted chaperone TM1083 in T. maritima is thought to stabilize the DNA gyrase enzyme at temperatures near optimal growth (Canaves 2004). Moreover, the molecular chaperone trigger factor (TM0694) from T. maritima strongly binds model proteins and decreases their folding rate, while these activities are much weaker in the homologous trigger factor from the psychrophile Pseudoalteromonas haloplanktis, which instead shows increased prolyl isomerization (Godin-Roulling et al 2015). However, it should be noted that chaperones, although always highly expressed in thermophiles, are part of their high temperature response as well.…”
Section: Protein Dynamics and Turnover; Assistance From Chaperones Anmentioning
confidence: 99%
“…For example, the predicted chaperone TM1083 in T. maritima is thought to stabilize the DNA gyrase enzyme at temperatures near optimal growth (Canaves 2004). Moreover, the molecular chaperone trigger factor (TM0694) from T. maritima strongly binds model proteins and decreases their folding rate, while these activities are much weaker in the homologous trigger factor from the psychrophile Pseudoalteromonas haloplanktis, which instead shows increased prolyl isomerization (Godin-Roulling et al 2015). However, it should be noted that chaperones, although always highly expressed in thermophiles, are part of their high temperature response as well.…”
Section: Protein Dynamics and Turnover; Assistance From Chaperones Anmentioning
confidence: 99%
“…52 In the present paper, we describe the cloning, expression and purification of a c-CA identified in the genome of Pseudoalteromonas haloplanktis (formerly known as Alteromonas haloplanktis) 53 which is an obligate aerobic Gram-negative rod-like bacterium, isolated from seawater sampled along the Antarctic ice shelf. 54,55 The analysis of genomic DNA from the aforementioned psychrophilic bacterium revealed that it encodes CAs belonging to the b-and c-classes. Intriguingly, also the genome of this Gramnegative bacterium does not encode for a periplasmic a-CA, as seen for other Gram-negative bacteria and as mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, K. olearia has three temperature-responsive peptidylprolyl isomerase (PPIase) genes: two PpiC-type genes (Kole_1682 and Kole_0383) that are both highly expressed at 40 °C, and one FKBP-type gene (Kole_1745) that shows high expression at all temperatures except 77 °C (Table S5). At lower temperatures (e.g., 37 °C), these enzymes catalyze proline isomerization, which happens spontaneously at higher temperatures (Godin-Roulling et al 2015 ). However, the enzymes known to assist protein folding under cellular stress, chaperones [GroEL (Kole_1627) and Hsp70 (Kole_0886)] and protease Do (Kole_1599), were significantly down-regulated at 40 °C (Table S5; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At the moderately sub-optimal growth temperature of 40 °C, K. olearia cells face physiological challenges of proper protein folding (Godin-Roulling et al 2015 ), and of maintenance of a functional cell membrane (de Mendoza 2014 ). Our observation that at 40 °C, despite the lower growth rate, lipid metabolism genes were among the most highly expressed genes suggests that changes to the cell membrane composition are one of the most important adaptations for survival of K. olearia at lower temperatures.…”
Section: Discussionmentioning
confidence: 99%